PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT. BANK MANDIRI (PERSERO) TBK. AREA MANADO - Jesica E.Y. Undap (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2022)
In the era of the industrial revolution 4.0, it becomes a challenge for every company to compete with each other to show quality products. The purpose of this study is to find out the Influence of Discipline and Supervision on Employee Performance on PT. Bank Mandiri (Persero) Tbk. Manado area. This type of research is quantitative research and research methods using descriptive research methods. The study took samples from one population using questionnaires as a data collection tool. The population is taken by employees of PT. Bank Mandiri (Persero) Tbk. Manado area. The employees in question amounted to 78 employees but the sample involved amounted to 37 respondents using the Simple Random Sampling method. The analysis used is Descriptive Statistical Analysis, Total Score, Multiple Linear Regression Analysis, and Correlation. The results of the study's study the simultaneous correlation coefficient value r = 0.663 showed that Discipline and Supervision had a strong and significant relationship to improved employee performance at PT. Bank Mandiri (Persero) Tbk. Manado area. The coefficient of determination indicates that an increase in employee performance, 44% are influenced by discipline and supervision together, while the remaining 56% is influenced by other factors. The results of the analysis showed that Discipline and Supervision had a significant influence on improving employee performance at PT. Bank Mandiri (Persero) Tbk. Manado area. For this reason, Discipline and Supervision need to be considered and maximized by the leadership and the company by paying more attention to internal and organizational factors regarding Discipline and Supervision to improve employee performance